The Predictors of Competitive Advantage Among F&B MSMEs in Post-Pandemic Era - Calvin Kurniawan; Kartika Nuringsih (International Journal of Application on Economics and Business, 2023)
This study aims to analyze the effect of entrepreneurial orientation, dynamic capabilities, and market orientation on competitive advantage in Food & Beverage Micro, Small, and Medium Enterprises (MSMEs) in Jakarta. The research method used is a quantitative method with multiple linear regression analysis. The research sample was taken based on a survey technique with 123 respondents collecting questionnaires. The data obtained were processed using the Smart-PLS program. The results of the analysis in this study indicate that entrepreneurial orientation has a positive and insignificant effect on competitive advantage. Meanwhile, dynamic capabilities and market orientation have a positive and significant impact on competitive advantage. This research is expected to be useful for MSMEs as information, understanding, and insight in improving the ability of entrepreneurial orientation, dynamic capabilities, and market orientation by building a competitive advantage strategy in the face of transformation in the period after the pandemic in Jakarta.